The Financial Balance Policy Between Central and Local Government: Toward More Just Financial Allocation - M. Fabian Akbar; Irvan Mareto; Alfido Fiqri Arsy Adhiem; Ayi Dudi Firdaus; Adriana Maisarah binti Mohd Farid (Universitas Airlangga, 2023)
Government finance policy in Indonesia has become an issue that leads to corruption in Indonesia. Remembering that Indonesia is a unitary rather than a parliamentary country, the financial distribution must come from the center of the government, which in most cases leads to corruption since the allocation of the finance does not arrive in the hands of the local government based on the real number. It is interesting to discuss the system that governs the financial distribution from the central government to the local government, and the problems that arise within the system itself. This paper will discuss the financial distribution system from the central government to the local government, as well as the problems that arise within the system that has been used by Indonesia since its establishment. In addition, an example of a case will be discussed here to provide a deeper understanding of the readers. Therefore, a good understanding towards the idea of financial balance between central and local governments will be achieved by the readers.